Detection of anti-Candida antibodies by the indirect immunofluorescence assay in patients with cancer in the orofacial region - Dorko, E; Jenca, A; Pilipcinec, E; Tkáciková, L (Folia microbiologica, 2002)
An indirect immunofluorescence assay was performed to detect antibodies to Candida albicans blastospores and germ tubes. Serum specimens were obtained from 82 patients with neoplastic diseases in the orofacial region and thrush of the oral mucosa. C. albicans was identified in the oral cavity of 63 patients investigated but serum anti-Candida antibodies were detected in only 23 of them. Serological examination showed that titers of antibodies to C. albicans blastospores ranged from 1:20 to 1:1280. High titers from 1:640 to 1:1280 were detected in patients without antibiotic, cytostatic, or radiotherapeutic treatment. The titers of antibodies to C. albicans germ tubes ranged from 1:20 to 1:640. Our results indicate that titers of antibodies to the C. albicans germ tubes were lower and were detected in a smaller number of patients.
Keywords: Mouth Mucosa; Candidiasis, Oral; Carcinoma; lidé; kandidóza; protilátky fungální; ústní sliznice; Female; orální kandidóza; Fluorescent Antibody Technique, Indirect; Humans; karcinom; fluorescenční protilátková technika nepřímá; mužské pohlaví; Candidiasis; Antibodies, Fungal; ženské pohlaví; Male; nádory úst; Candida albicans; Mouth Neoplasms